-symmetric model with an interplay between kinematical and dynamical non-localities. (22nd April 2015) - Znojil, Miloslav
Abstract: A new family of non-Hermitian -symmetric quantum models is proposed in which the Hamiltonians are finite-dimensional and in which the dynamical-input potential V is multi-parametric and non-local. The choice is supported by the exact solvability of Schrödinger equation and by the well known fact that in -symmetric models a non-locality is already present due to the generic kinematical non-diagonality of the Hermitizing metrics Θ . For a subfamily of our H s, also all of the eligible metrics Θ appear obtainable in closed form.